Understanding the determinants of cryptocurrencies adoption among young Malaysians - Saidi, Mpawenimana Abdallah; Tang, Seik Yng; Olowolayemo, Akeem; Adewale, Nafisah; Mohammed, Adam Andani (Kulliyyah of Information and Communication Technology, IIUM, 2023)
Currently around the world and especially in Malaysia, digital currencies are still in their nascent stage, especially among university students. Several groups like government establishments, the business community, and young generations among others have started to take considerable interest in the use of digital currencies for different forms of transactions. However, the potential of cryptocurrencies has not been entirely exploited to its fullest. This study examined the impact of digital currency adoption on the Malaysian economy through a quantitative design using an online survey. The population for this study includes young, educated people in Malaysia, specifically undergraduates and young graduates. This research evaluates Malaysian university students' and young graduates’ awareness and usage of cryptocurrencies as well as the challenges envisaged by various strata of users regarding the impact of digital currency adoption on the economy and the future of banking and money. The findings show that statistically significant positive relationships exist between the dependent variable (Intention to use Cryptocurrencies) and all independent variables of the study,(namely, awareness, perceived ease of use, perceived usefulness, perceived trustworthiness as well as perceived risk), and the dependent variable, intention to use (IU)(with correlation coefficient r-values of 0.106 and 0.164 with the p-value is 0.000 and significance level of 0.01). The study therefore concludes that the potential of cryptocurrencies invading the global market, despite the advantages of cryptocurrencies, is yet to be widely accepted among Malaysians.